A deterministic approach for predicting the transformation of starch suspensions in tubular heat exchangers. (February 2016) - Plana-Fattori, A.; Flick, D.; Ducept, F.; Doursat, C.; Michon, C.; Mezdour, S.
Abstract: Numerical modeling of fluid flow, heat transfer and transformation is conducted for an aqueous suspension of starch granules running throughout a four-heating-section tubular exchanger. The numerical model considers the transformation kinetics and the rheological behavior of the starch suspension as determined from laboratory work; further, the model includes the geometrical characteristics of the heat exchanger, as well as the operating conditions which were considered in running it. Model predictions are compared with results from experimental work, after sampling the starch suspension under thermal processing and later characterizing it using laboratory techniques. The numerical model predicts the bulk swelling state of the starch suspension at a level of agreement (−41% in volume mean diameter increase) which is better than the one reached after assuming plug-flow and radially-independent temperature (−66%). The inclusion of two-way coupling between the relevant phenomena constitutes therefore a positive improvement. Highlights: Fluid flow, heat transfer and starch swelling are coupled in a numerical model. Kinetics and rheology of starch suspension swelling were obtained experimentally. Dynamic, thermal and swelling conditions were studied in a tubular heat exchanger. Experimental results from the heat exchanger agree well with model predictions. Model predictions become worse when assuming radially-independent temperature.